Exploring family, community and healthcare provider perceptions and acceptability for minimal invasive tissue sampling to identify the cause of death in under-five deaths and stillbirths in North India: a qualitative study protocol - Manoja Kumar Das; Narendra Kumar Arora; Reeta Rasaily; Harish Chellani; Harsha Gaikwad; Kathryn Banke (BMC, 2019)
Abstract Background Around 5.4 million under-five deaths occur globally annually. Over 2.5 million neonatal deaths and an equivalent stillbirths also occur annually worldwide. India is largest contributor to these under-five deaths and stillbirths. To meet the National Health Policy goals aligned with sustainable development targets, adoption of specific strategy and interventions based on exact causes of death and stillbirths are essential. The current cause of death (CoD) labelling process is verbal autopsy based and subject to related limitations. In view of rare diagnostic autopsies, the minimally invasive tissue sampling (MITS) has emerged as a suitable alternate with comparable efficiency to determine CoD. But there is no experience on perception and acceptance for MITS in north Indian context. This formative research is exploring the perceptions and view of families, communities and healthcare providers regarding MITS to determine the acceptability and feasibility. Methods The cross-sectional study adopts exploratory qualitative research design. The study will be conducted in New Delhi linked to deaths and stillbirths occurring at a tertiary care hospital. The data from multiple stakeholders will be collected through 53-60 key-informant in-depth interviews (IDIs), 8 focus group discussions (FGDs) and 8-10 death or stillbirth event observations. The IDIs will be done with the parents, family members, community representatives, religious priests, burial site representatives and different health care providers. The FGDs will be conducted with the fathers, mothers, and elderly family members in the community. The data collection will focus on death, post-death rituals, religious practices, willingness to know CoD, acceptability of MITS and decision making dynamics. Data will be analysed following free listing, open coding, selective coding and theme identification. Subsequently 8-10 parents will be approached for consent to conduct MITS using the communication package to be developed using the findings. Discussion The study will provide in-depth understanding of the cultural, social, religious practices related to child death and stillbirth and factors that potentially determine acceptance of MITS. The findings will guide development of communication and counselling package and strategies for obtaining consent for MITS. The pilot experience on obtaining consent for MITS will inform suitable refinement and future practice.